Effects of the new standardised approach and the new output floor for IRB banks - Henrik Andersen; Jama Johnsen (Norges Bank, 2023)
The EU plans to revise the capital adequacy rules for banks in 2025. Regulatory amendments will be introduced in Norway through the EEA Agreement. Our results show that the regulatory amendments can significantly reduce the capital requirement for small and medium-sized banks (SA banks). This may enable SA banks to offer cheaper loans. The new rules will have limited implications for the largest Norwegian banks (IRB banks), but they may contribute to more equal and comparable capital requirements for Norwegian and foreign banks. Overall, the regulatory amendments may therefore level the playing field for banks in Norway.
hdl:11250/3073121
Keywords: 330; Banks; the standardised approach (SA); the IRB approach; lending and lending margins